A Multiwavelength View of the Neutron Star Binary 1FGL J1417.7-4402: A Progenitor to Canonical Millisecond Pulsars - Swihart, S.; Strader, J.; Shishkovsky, L.; Chomiuk, L.; Bahramian, A.; Heinke, C.; Miller-Jones, James; Edwards, P.; Cheung, C. (Institute of Physics Publishing, 2018)
The Fermi γ-ray source 1FGL J1417.7–4407 (J1417) is a compact X-ray binary with a neutron star primary and a red giant companion in a ~5.4 days orbit. This initial conclusion, based on optical and X-ray data, was confirmed when a 2.66 ms radio pulsar was found at the same location (and with the same orbital properties) as the optical/X-ray source. However, these initial studies found conflicting evidence about the accretion state and other properties of the binary. We present new optical, radio, and X-ray observations of J1417 that allow us to better understand this unusual system. We show that one of the main pieces of evidence previously put forward for an accretion disk—the complex morphology of the persistent Hα emission line—can be better explained by the presence of a strong, magnetically driven stellar wind from the secondary and its interaction with the pulsar wind. The radio spectral index derived from VLA/ATCA observations is broadly consistent with that expected from a millisecond pulsar, further disfavoring an accretion disk scenario. X-ray observations show evidence for a double-peaked orbital light curve, similar to that observed in some redback millisecond pulsar binaries and likely due to an intrabinary shock. Refined optical light-curve fitting gives a distance of 3.1 ± 0.6 kpc, confirmed by a Gaia DR2 parallax measurement. At this distance the X-ray luminosity of J1417 is (1.0-0.3+0.4) ×10 33 erg s−1, which is more luminous than all known redback systems in the rotational-powered pulsar state, perhaps due to the wind from the giant companion. The unusual phenomenology of this system and its differing evolutionary path from redback millisecond pulsar binaries points to a new eclipsing pulsar "spider" subclass that is a possible progenitor of normal field millisecond pulsar binaries.